DETECTION OF MULTIDRUG-RESISTANT Klebsiella pneumoniae IN THE UPPER RESPIRATORY TRACT OF BROILERS AND LAYER CHICKENS FROM COMMUNITY FARM IN ACEH BESAR, INDONESIA - AK, M Daud; Darniati, Darniati; Erina, Erina; Abrar, Mahdi; Zainuddin, Zainuddin (Universitas Syiah Kuala, 2025)
This study aimed to investigate the presence of multidrug-resistant (MDR) Klebsiella pneumoniae in upper respiratory tract of broiler chickensand laying hens from community farms in Aceh Besar. Tracheal swab samples were collected and cultured on eosin methylene blue agar for bacterialisolation. Suspected isolates were identified through biochemical testing and confirmed via PCR targeting the rpoB gene. Identified isolates weretested for antibiotic susceptibility against ciprofloxacin, tetracycline, gentamicin, erythromycin, and chloramphenicol, using the disc diffusionmethod. The results revealed K. pneumoniae in 6% of broiler and 14% of laying hens, with widespread multidrug resistance. All isolates wereresistant to erythromycin (100%), gentamicin (100%), tetracycline (85%), ciprofloxacin (40%), and chloramphenicol (15%). These findingsconcluded that there has been the spread of MDR of K. pneumoniae in broiler chickens and laying hens within Aceh Besars community farms inAceh Besar, Indonesia.